A construção do critério quantitativo da regra-matriz sancionatória por decisão judicial - Peres Júnior, José Orivaldo (2024)
The doctoral thesis, that we submit to the Board of Examiners of the Graduate Program in Tax Law of the Pontifical Catholic University of São Paulo, aims to analyze the issue of tax sanctions declared unconstitutional by the courts, its effects and consequences, in the light of the Post Law, especially in relation to the reduction of the amount of tax fines under the same pronouncement. Using the analytical-hermeneutic method, in the doctrinal line of “logicalsemantic constructivism”, together with the premises set in this work, we will approach the legal system in a foreground, in view of its completeness and consistency, with emphasis on the constitutional principles of security and legality that are the “pillars” of any and all legal plexus, in addition to the principle of non-confiscation, for being attached to the core of our study. Therefore, we consider it essential to go through the aspects involving the institutes of the legal norm, the rule-matrix of tax incidence sanctioning with their species, the phenomenon of normative incidence, the sources of law and the sources of positive law, as well as the hierarchy of “laws” and the necessary primary introductory vehicle for the institution of tax sanctions. Then, within a Dialogism consistent with the work developed so far, the study turns to reasoning and to the argumentation of judicial decisions declaring unconstitutionality (of tax sanctions), given the techniques available in the ordering (pronunciation of nullity, according to the Constitution and without text reduction – article 927, § 3º, of the Code of Civil Procedure, combined with article 27 of Law n. 9.868/99), which is fundamental to our conclusions. By examining the judgments of the Supreme Court, we find an oscillating and undefined jurisprudence on the issues related to tax sanctions, maximum pending judgment on various issues. The desideratum is to establish the limits and scope of the decisions of the Judiciary when the recognition of the unconstitutionality of the norm sanctioning for violation of the principle of non-conforcement and in which situations and conditions the legal system allows the moderation or reduction of tax fine by the court. In this sense, the concern that affects us is with regard to the increasing interventionism of the Judiciary Power in the face of the what should be presented proposal for stabilization of harmony between the Political Powers on the subject of tax sanctions, since the system already has integrative rules for the dosimetry sanctioning, but not self-administered. Indeed, we point out that the editing of structure rules regulating the assumptions for the graduation of the tax penalty is rigorous, so that constitutional principles conferred on taxpayers are implemented, individualization of the tax penalty. The study developed was based on the indicated bibliography and jurisprudence of several historical periods, seeking a logical, systematic and consistent triggering, through objective and well-defined conclusions, without losing sight of the preservation of the legal system and, ultimately, legal certainty